Athens and Boiotia - van Wijk, Roy (Cambridge University Press, 2024)
Are Greek neighbours natural enemies in the Archaic and Classical period? This book uses literary, archaeological and epigraphic sources to reveal that the neighbours Attica and Boiotia had a more complex and positive relationship than has been assumed until now. This title is also available as Open Access on Cambridge Core.